Executive coaching : lead, develop, retain, motivated, talented people - Stephenson, Peter (Sydney : Pearson Education, 2000)
This book is about: Setting the scene for executive coaching; Executive effectiveness: myths and realities; Talent management; Where executive coaching adds values; ...
Keywords: Management; Leadership; Leadership; Executives -- Training of; Management -- Study and teaching